Dimensionality of Policy Space in Consociational Northern Ireland. - Garry, John; Matthews, Neil; Wheatley, Jonathan (Political Studies, 2017)
A criticism of consociational power sharing as an institutional response to violent conflict is that it buttresses rather than ameliorates the underlying (linguistic, religious or ethno-national) divide, hence prohibiting the emergence of new dimensions of political competition (such as economic left-right or moral liberal-conservative dimensions) that are characteristic of 'normal' societies. We test this argument in the context of the illustrative Northern Ireland case, using data from expert coding of party policy documents and opinion data derived from two Voter Advice Applications (VAAs). We find evidence for a moral liberal-conservative dimension of politics in addition to the ethno-national dimension. Hence, we caution against assuming that consociational polities are unidimensional.